2021
DOI: 10.3390/cells10123487
|View full text |Cite
|
Sign up to set email alerts
|

Orai3 Calcium Channel Regulates Breast Cancer Cell Migration through Calcium-Dependent and -Independent Mechanisms

Abstract: Orai3 calcium (Ca2+) channels are implicated in multiple breast cancer processes, such as proliferation and survival as well as resistance to chemotherapy. However, their involvement in the breast cancer cell migration processes remains vague. In the present study, we exploited MDA-MB-231 and MDA-MB-231 BrM2 basal-like estrogen receptor-negative (ER−) cell lines to assess the direct role of Orai3 in cell migration. We showed that Orai3 regulates MDA-MB-231 and MDA-MB-231 BrM2 cell migration in two distinct way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Ca 2+ imaging acquisition was performed as previously described [ 61 ]. Briefly, 25 × 10 3 transfected PANC-1 cells were seeded on glass coverslips 72 h before each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ imaging acquisition was performed as previously described [ 61 ]. Briefly, 25 × 10 3 transfected PANC-1 cells were seeded on glass coverslips 72 h before each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The 8 × 10 4 transfected PANC-1 cells were seeded on coverslips 72 h before the proximity ligation assay (PLA) experiment. As described before [ 61 ], cells were washed with PBS and fixed with PFA (4%) at room temperature for 20 min. Thereafter, cells were washed and permeabilized with 0.1% Triton TM X-100 (Sigma, Saint-Quentin-Fallavier, France) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It enhances gastric cancer cell metastasis by inducing FAK-mediated MAPK/ERK activation and promotes the dissociation of focal adhesions at the posterior margin of cells (Wu et al, 2021b). Studies on Orai3 calcium channels have revealed that Orai3 alters cell adhesion capacity in two ways: 1) by reducing calpain activity, cell adhesion, and migration in a calcium-dependent manner and 2) via interaction with FAK to regulate the actin cytoskeleton (Chamlali et al, 2021), which is the main driver of cell adhesion and mechanosensing in a Ca 2+independent manner. (Pedrosa et al, 2019), fibroblasts (Demircioglu et al, 2020), and adipocytes (Blücher et al, 2020) surrounding the tumor can also contribute to the shaping of the TME by activating FAK-related pathways.…”
Section: Focal Adhesion Kinase Epithelialmesenchymal Transition and I...mentioning
confidence: 99%
“…Considering Orai channels, many studies have described a correlation between the expression and activity of these channels and the cellular hallmarks associated with different cancer types. Then, as it has been proposed that Orai3 is involved in the regulation of G1 phase and G1/S transition in tumor cells (Chamlali et al, 2021; Sanchez‐Collado, Jardin et al, 2021), Faouzi et al aimed to elucidate the relationship between Orai3 and c‐myc. To identify the connection between them, authors have simultaneously compared the expression of both proteins in breast cancer tumor samples and cell lines.…”
Section: C‐mycmentioning
confidence: 99%